Waste Water Treatment Technology by The Anaerobic with IC Reactor - NURISLAMIYATI, DINDA ULZANAH; MILANA, LIA (Universitas Majalengka, 2022)
In this industrial 4.0 era, there are more industries built in Indonesia. During the operation of an industry, the waste generated is not spared. These industrial wastes, if not managed properly, can pollute the environment and can endanger the environment and health. The waste treatment process can be done in several ways, such physically, chemically and biologically. With the smart city concept, the government, society, industry, transportation and also the environment must be smart, especially in utilizing existing resources so that they can be used efficiently and effectively. For the development of waste treatment technology and to fulfill this concept, the industry must also play a role in choosing an efficient technology. Therefore, to utilize energy effectively and efficiently, in handling liquid waste from industrial production, anaerobic waste treatment technology using IC (Internal Circulation) Reactor can be used. IC Reactor is considered as an excellent and efficient technology development breakthrough. This technology uses 3-phase separation to produce gas, biomass and final waste. In this technology, in addition to cleaning waste water, biogas is also produced at the same time which can be used as a reusable resource. In addition, this technology can also save costs and energy, so that the waste treatment process using an IC Reactor is a very effective and efficient treatment method.